Foreword for the special issue on the Tenth International Workshop on Low Energy Electron Microscopy and Photoemission Electron Microscopy - Schmid, Andreas; Scholl, Andreas (Ultramicroscopy, 2017)
The Tenth International Workshop on Low Energy Electron Microscopy and Photoemission Electron Microscopy (LEEM/PEEM-10) was hosted in Monterey, California on September 11–15, 2016. This Workshop marked the 18th anniversary of the LEEM/PEEM series. The inaugural LEEM Workshop was organized by Ernst Bauer, the inventor of LEEM, and was held 1998 in Tempe, Arizona, USA. Since then this biennial series of meetings was held in locations rotating between America, Asia and Europe. The workshop series is designed to review the status of LEEM, PEEM, SPLEEM, XPEEM and related techniques, and to promote and disseminate applications of cathode lens microscopy to a broad audience of interested scientists. Highlighting the most recent scientific advances and instrumental developments, the LEEM/PEEM-10 meeting was attended by 114 researchers from 17 countries and featured sessions discussing new results on properties of surfaces, thin films, organic films, as well as surface chemistry, magnetism, time resolved methods and instrumental advances and novel applications of LEEM and PEEM to other subject areas.